Festa do divino espiríto santo na região do gameleira - Reis, Mariana Rodrigues dos (Universidade Federal do Tocantins, 2021)
The Divino Espírito Santo festival is a Catholic religious festival that is a tradition in the State of Tocantins, including in the district of Gameleira, municipality of Silvanopolis -TO. It is a party that presents a manifestation of popular religiosity and that has great popular representation. So, this article aimed to describe how the Divino Espírito Santo festival is held in the region of Gameleira, Silvanópolis -TO. The methodology used was the field research carried out in the district of Gameleira, municipality of Silvanópolis - TO, from January to July 2019. To collect the information, interviews were conducted with the party participants and participation in the party of the year 2019.The results showed that the party of Divino Espírito Santo in the region of Gameleira has its origin in the year 1984, and in 2019 the party took place on July 12 and 13. In the end it was concluded that revelers celebrate the Divine Espírito Santo in the region of Gameleira, usually in the month of July of each year.